2014
DOI: 10.1371/journal.pone.0088091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of the Major Peanut (Arachis hypogaea L.) Cultivars Grown in China by SSR Markers

Abstract: One hundred and forty-six highly polymorphic simple sequence repeat (SSR) markers were used to assess the genetic diversity and population structure of 196 peanut (Arachis Hypogaea L.) cultivars which had been extensively planted in different regions in China. These SSR markers amplified 440 polymorphic bands with an average of 2.99, and the average gene diversity index was 0.11. Eighty-six rare alleles with a frequency of less than 1% were identified in these cultivars. The largest Fst or genetic distance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 52 publications
(77 reference statements)
7
55
3
1
Order By: Relevance
“…The 111 SSRs detected a total of 472 alleles, the number of alleles per marker detected ranged from 2 to 9 with an average of 4.25 per locus and this result is in agreement with those of the previous genetic diversity studies. Ren et al () reported the results of 2 to 9 alleles with an average of 3.0 alleles per locus, Roomi et al () resulted in 2 to 4 alleles with an average of 2.6 alleles per locus, and Pandey et al () observed 2 to 14 alleles per locus with an average of 3.2. Most of the studies reported 2–8 alleles per locus, compared to higher alleles of 2–13 alleles of Song et al (), 2–20 alleles of Varshney et al () and 3–15 alleles of Naito et al ().…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 111 SSRs detected a total of 472 alleles, the number of alleles per marker detected ranged from 2 to 9 with an average of 4.25 per locus and this result is in agreement with those of the previous genetic diversity studies. Ren et al () reported the results of 2 to 9 alleles with an average of 3.0 alleles per locus, Roomi et al () resulted in 2 to 4 alleles with an average of 2.6 alleles per locus, and Pandey et al () observed 2 to 14 alleles per locus with an average of 3.2. Most of the studies reported 2–8 alleles per locus, compared to higher alleles of 2–13 alleles of Song et al (), 2–20 alleles of Varshney et al () and 3–15 alleles of Naito et al ().…”
Section: Discussionmentioning
confidence: 99%
“…In this study, most of the peanut lines were released cultivars, and some were breeding lines, so the allele number per locus would be similar to that of released cultivars (Jiang et al ). There is a report suggesting that there is less genetic diversity in released cultivars than landraces (Ren et al ). This study is in agreement with Ren et al () that the 111 SSR markers are effective and useful for analyzing the genetic diversity of peanut breeding lines, germplasm, and released cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AhTE markers could be successfully used to group the genotypes based on the principal co-ordinates. Therefore, AhTE markers might provide an efficient marker system, like SSR markers (Li et al, 2011;Ren et al, 2014), for genetic and genomic studies in groundnut. Recently, AhTE markers have been successfully employed for trait mapping in groundnut (Shirasawa et al, 2012b;Kolekar et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the true optimal number of subsets (K) in STRUCTURE, LnP(D) and DK were chosen, as described in Ren et al [45]. The K value that provides the maximum likelihood, called LnP(D) in STRUCTURE, is generally considered as the optimal number of subdivisions [37].…”
Section: Novel Ssr Markers and Genetic Diversity In S Lazicamentioning
confidence: 99%